Analysis of Relationship between Military Connection and Quality of Financial Report - Balqis Nagita Fillia Zunaedi; Novrys Suhardianto (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purpose of this study is analysis of relationship between military connection and quality of financial report. The research approach used in the research is a quantitative approach. The population of this research data is all non-financial companies listed on the Indonesia Stock Exchange during the 2015-2019 period. The total sample is 1,394. This study uses multiple linear regression. The results of this study indicate that military connection has no relationship with quality of financial report. The proportion of directors who are military connection is negative relationship to quality of financial report.